The Union of South Africa censuses 1911 - 1960 : an incomplete record (Historia, 2021)
The census is one of the most intrusive and comprehensive investigations undertaken by the state in its quest for information concerning the population  it controls and serves. The information sought is more than a mere headcount. It reflects the official need for statistics on a wide range of human activities and attributes, in order to execute the functions of the modern bureaucratic state because it came into being in the nineteenth and twentieth centuries. Census questionnaires require not only purely demographic statistics on the number of people by sex, age and marital status, but also economic information on education, occupation, and income and most contentiously on questions of identity including race, language, religion and nationality. Indeed it was the census authorities who through the collection and tabulation of vast quantities of individual items of data, provided: "the descriptions which 'speak to power' with 'useful' information". In order to make the data intelligible to the state bureaucracy it was necessary to simplify and to classify the population into defined categories or groups, for which the census authorities also possessed the prerogative of naming.
Keywords: The Union of South Africa; 1911 - 1960; sex; age; marital status; education; occupation; race; language